Privalization and democracy: the effects of regime type in the developing world. - Biglaiser, Glen; Danis, Michelle A. (2002)
What is the effect of regime type on privatization of state-owned enterprises? The authors investigate the relationship between regime type and privatization through a panel data set for developing countries from 1987 to 1994.The results show that, contrary to most studies the claim that authoritarian regimes are better able to ignore societal interests opposed to economic measures that impose austerity, democracies privatize more than authoritarian regimes. Moreover, challenging conventional interpretations that claim that economic difficulties contributed state sell-offs, the authors find that privatization is most likely in wealthier developing democracies whose budgets operate with current account surpluses. Hence authoritarian regimes provide neither the right nor the correct model for countries wishing to pursue unpopular economic policies. -Reproduced.
Keywords: Democracy